Heat Transfer, Volume 3 2006
DOI: 10.1115/imece2006-14073
|View full text |Cite
|
Sign up to set email alerts
|

Smoothed Particles Hydrodynamics Method for Interaction Between Multi-Droplets and Substrate

Abstract: The smoothed particle hydrodynamics (SPH) method, one of meshfree methods, is developed to simulate the interaction between multi-droplets and substrate with solidification. However, the SPH method for this complicated problem needs a large amount of computing time, since it has to use a large number of the SPH particles to represent multidrops and substrate. All-pair search and linked list algorithms are popular in the neighbor search, which is the most time consuming part of the SPH calculation. Both algorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The SPH method is a mesh-free Lagrangian method for simulating fluid flows and natural phenomena that involve complex deformations, free surface flows, and moving particles. Because of its advantage, the SPH method has been applied to study various multiphase fluid problems [18,[20][21][22][23][24][25][39][40][41][42][43][44]. The SPH method was applied to investigate the effects of contact angle and surface tension on the outcome of the YSZ droplet impact [20]; they found that the impact angle is less than 44°, and the droplet splash occurred.…”
Section: Smoothed Particle Hydrodynamics (Sph) Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SPH method is a mesh-free Lagrangian method for simulating fluid flows and natural phenomena that involve complex deformations, free surface flows, and moving particles. Because of its advantage, the SPH method has been applied to study various multiphase fluid problems [18,[20][21][22][23][24][25][39][40][41][42][43][44]. The SPH method was applied to investigate the effects of contact angle and surface tension on the outcome of the YSZ droplet impact [20]; they found that the impact angle is less than 44°, and the droplet splash occurred.…”
Section: Smoothed Particle Hydrodynamics (Sph) Methodsmentioning
confidence: 99%
“…The SPH method was applied to investigate the effects of contact angle and surface tension on the outcome of the YSZ droplet impact [20]; they found that the impact angle is less than 44°, and the droplet splash occurred. To investigate the solidification process resulting from the impacts of multiple droplets, an improved SPH method was employed and showed that the SPH formulation could predict the complex process, including the melting of the substrate during the impact [43,44]. A correlation between the splash threshold and the kinetic energy was investigated by comparing with experimental data.…”
Section: Smoothed Particle Hydrodynamics (Sph) Methodsmentioning
confidence: 99%